A comparison of forage yield and quality in a simulated graze-out for twelve varieties of hard red and white winter wheat - R.L. Hale; C.T. Thompson; C.T. MacKown; Troy J. Dumler (Kansas Agricultural Experiment Station Research Reports, 2005)
Six hard white winter wheat varieties (Burchett, Lakin, NuFrontier, NuHills, Nu- Horizon, and Trego) and six hard red winter wheat varieties (2137, Jagalene, Jagger, OK101, Stanton, and Thunderbolt) were planted in two southwestern Kansas counties, Clark and Stanton, to compare simulated graze-out forage yield and quality. Four replicated plots were planted in September 2003 for each variety at each location. Forage samples were collect from each plot during December 2003, March 2004, and April or May 2004. Dry matter content, dry matter yield, crude protein, acid detergent fiber (ADF), neutral detergent fiber (NDF), total digestible nutrients (TDN), net energy (NEm, NEg), relative feed value (RFV), and nitrate nitrogen were determined. Significant location-by-variety interactions were observed for most factors. Although significant differences in crude protein and energy were detected, it is unlikely that the performance of stock cattle would differ when grazing each of the varieties because the lowest crude protein concentration would support excellent gain, and because the differences in energy were relatively small.
Keywords: Cattlemen& #x27; s Day; 2005; Kansas Agricultural Experiment Station contribution; no. 05-144-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 943; Beef; Forage yield; Hard red winter wheat; White winter wheat